Internalisasi Nilai Lontar Sarasamuscaya Melalui Ekopedagogi Hindu dalam Menumbuhkan Etika Pengelolaan Sampah - Ni Putu Gatriyani (Jurnal Penelitian Agama Hindu, 2026)
The increasingly complex problem of waste has become a serious challenge in maintaining environmental balance and indicates that the ecological crisis stems not only from technical aspects of waste management but also from the weakening of human moral and spiritual awareness. This condition requires an educational approach that emphasizes not merely cognitive aspects, but also the formation of ecological ethics and character among learners. In the context of Hindu education, the Lontar Sarasamuscaya contains ethical teachings such as, karuna, and dharma, which are relevant for fostering ecological awareness through a Hindu ecopedagogical approach.This study aims to analyze the process of internalizing the values of Lontar Sarasamuscaya through Hindu ecopedagogy in shaping waste management ethics and ecological awareness among students at STKIP Agama Hindu Amlapura. The research employs a qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews, and analysis of learning documents and campus environmental programs. Data analysis was conducted thematically using an interactive model consisting of data reduction, data display, and conclusion drawing.The results show that the internalization process occurs through three main stages: value transformation in the form of students’ cognitive understanding of Sarasamuscaya teachings related to waste issues; value transaction through affective engagement in social practices and environmental management activities; and transinternalization marked by changes in ecological behavior and the formation of an environmentally conscious campus culture. The values of ahimsa, karuna, and dharma are manifested in habits such as waste segregation, reducing the use of plastic, and interpreting cleanliness as a spiritual practice.The conclusion confirms that the integration of Sarasamuscaya teachings within Hindu ecopedagogy effectively fosters students’ ecological character in a sustainable manner and strengthens the relevance of Hindu religious education in addressing contemporary environmental crises.